Generation of early-flowering Chinese cabbage (Brassica rapa spp. pekinensis) through CRISPR/Cas9-mediated genome editing - Jeong, So Young; Ahn, Hyomin; Ryu, Jahee; Oh, Youngbin; Sivanandhan, Ganeshan; Won, Kang-Hee; Park, Young Doo; Kim, Jin-Soo; Kim, Hyeran; Lim, Yong Pyo; Kim, Sang-Gyu (Plant biotechnology reports, 2019)
The CRISPR system enables us to induce precisely targeted mutations in a plant genome. The widely used CRISPR system is composed of a Cas9 protein derived from Streptococcus pyogenes (SpCas9) and a target site-specific guide RNA. In this study, we successfully generated the early-flowering Chinese cabbage ( Brassica rapa spp. pekinensis ), which is one of the most important vegetables in the world. To generate early-flowering B. rapa without requiring vernalization, we designed seven guide RNAs which target B. rapa homologous genes to the Arabidopsis thaliana FLOWERING LOCUS C ( FLC ). We first examined the indel mutation efficacy of the designed guide RNAs in protoplasts isolated from young leaves of Kenshin (an inbred line of B. rapa ). After selecting four guide RNAs, genome-edited plants were established by delivering the plant binary vectors harboring SpCas9 along with respective guide RNAs into B. rapa hypocotyl explants. In the T 0 generation, we found BraFLC2 and BraFLC3 double knockout lines with the indel efficiency of 97.7% and 100%, respectively. The simultaneous mutations of both BraFLC2 and BraFLC3 were inherited in T 1 generations with 100% of indel efficiency. The edited lines obtained showed an early-flowering phenotype that did not depend on vernalization. This study provides a practical gene-editing protocol for Chinese cabbage and verifies the function of its multi-copy BraFLC genes.